KOSAKATA SISTEM PERTANIAN TRADISIONAL SUNDA: KAJIAN STRUKTUR DAN MAKNA - Taufik Setyadi Aras (Ranah: Jurnal Kajian Bahasa, 2017)
Identity of Indonesia as agrarian country begins fading. A lot of the traditional farmers change their job to industrial sectors then impacting on behavior patterns of society to the environment and reducing the knowledge and skills in the traditional farming. The issues examined are the vocabulary of Sundanese traditional agricultural systems by using study the structure and semantics. The method used in this research is a qualitative descriptive method. This research applies some theories from Djajasudarma (2009 and 2013), Kridalaksana (2005), and Ramlan (1991). The results of this study that a category of vocabulary of Sundanese traditional agriculture systems divide into four classes, verbs and verbal, nouns and nominal, numeralia, derivative formand adjectives. The structure divides into two forms; base form and derivative form. Derivative form has four types, affixation, reduplication, acronym, and the combined of word. The meaning of vocabulary referring to tools and equipment, cultivation activities, circumstances and conditions of paddy, planting, place and crock, time, traditional ceremonies, community leaders’ rice pests, and size or dosage.ABSTRAKIdentitas Indonesia sebagai negara agraris mulai luntur. Tidak sedikit petani tradisional beralih pekerjaan ke sektor industri sehingga berdampak pada pola perilaku masyarakat terhadap lingkungan serta mengikis pengetahuan dan keterampilan dalam tata cara bertani tradisional. Masalah yang diteliti adalah kosakata sistem pertanian tradisional berbahasa Sunda dengan menggunakan kajian struktur dan makna. Metode yang digunakan adalah metode deskriptif kualitatif. Teori yang digunakan yaitu teori Djajasudarma (2009 dan 2013), Kridalaksana (2005), dan Ramlan (1991) . Berdasarkan penelitian, diketahui empat kelas kata yang ditemukan, yaitu verba(l), nomina(l), numeralia, dan adjektiva. Struktur kosakata ada dua bentuk, yaitu bentuk dasar dan turunan. Bentuk turunan ada empat, yaitu berdasarkan afiksasi, reduplikasi, akronim, dan gabungan kata. Makna kosakata mengacu pada peralatan dan perkakas, aktivitas penggarapan, keadaan dan kondisi padi, proses penanaman, nama tempat dan wadah, nama waktu, upacara tradisional, tokoh masyarakat, hama padi, serta ukuran atau takaran.